Sistem Yaklaşımına Dayalı Bir Metodoloji: Yumuşak Sistemler Metodolojisi - S Serap Kurbanoğlu (Türk Kütüphaneciliği)
This paper presents Soft Systems Methodology (SSM) which is based on systems approach and its associated ideas which are set out by Checkland. SSM has been developed for use in ill structured or messy problem contexts where there is no clear view on what constitutes the difficulties being experienced. There is a fundamental difference between these kind of problems (ill-structured, messy) and hard problems because in the latter the end or what should be achieved is already known. SSM is based on building a conceptual model following certain guide-lines. The conceptual model or the guide-lines can then be compared with the real-world or the current situation. The variance between the two, the conceptual model and the real- world, may then highlight the problems areas in which the solutions of these problems can be discussed or debated with the people in problem situation. SSM prevents decision makers from rushing into poorly thought-out solutions Ixised on preconceived ideas about an assumed problem. In the present paper the importance of avoding preconceived solutions and reaching real problems is also pointed out.